The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1128/aem.01568-13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Bacterial Community of the Chemically Defended Hawaiian Sacoglossan Elysia rufescens

Abstract: dSacoglossans are characterized by the ability to sequester functional chloroplasts from their algal diet through a process called kleptoplasty, enabling them to photosynthesize. The bacterial diversity associated with sacoglossans is not well understood. In this study, we coupled traditional cultivation-based methods with 454 pyrosequencing to examine the bacterial communities of the chemically defended Hawaiian sacoglossan Elysia rufescens and its secreted mucus. E. rufescens contains a defense molecule, kah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 72 publications
(65 reference statements)
1
33
0
Order By: Relevance
“…Symbiotic microbes typically supply nutrients to host animals that provide the microbes with shelter. Light production Squid Euprymna scolopes [109] Chemical defense Sacoglossan Elysia rufescens [110] Mollusks inhabit a variety of marine ecosystems. In environments characterized by poor nutrient contents, alternative strategies for nutrition have evolved.…”
Section: Contribution Of Symbionts To the Fatty Acid Pool Of Mollusksmentioning
confidence: 99%
“…Symbiotic microbes typically supply nutrients to host animals that provide the microbes with shelter. Light production Squid Euprymna scolopes [109] Chemical defense Sacoglossan Elysia rufescens [110] Mollusks inhabit a variety of marine ecosystems. In environments characterized by poor nutrient contents, alternative strategies for nutrition have evolved.…”
Section: Contribution Of Symbionts To the Fatty Acid Pool Of Mollusksmentioning
confidence: 99%
“…Overall, the data available for marine molluscs are not sufficient to evaluate the relative roles of geographic location and host identity in structuring the microbiome of a host. While studies focusing on microbiomes of multiple species at a particular site show that host identity plays a major role in determining microbiome composition (Davis et al, 2013;Aronson et al, 2017;Cicala et al, 2018), analyses of bivalves in aquaculture settings have shown that rearing the same host in different locations tends to change the relative abundances of a number of microbial phyla between individuals, which suggests that the external environment can also have a substantial effect on the composition of molluscan microbiomes (Trabal et al, 2012;Trabal Fernández et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the genus Vibrio are commonly found as part of the normal flora of molluscan intestinal tract (Oxley et al 2002;Davis et al 2013), thus making broodstock one of the principal sources of contamination in marine bivalve hatcheries. Several studies have been carried out on the gonads of reared mollusks revealed that they may be strongly infested with Vibrio (Lodeiros et al 1987;Llanos et al 2002;Sainz-Hernández et al 2005) which leads to the hypothesis of their vertical transmission between reproducers and gametes.…”
Section: Discussionmentioning
confidence: 99%